A study on the method and effect of the construction of a humanized mouse model of fecal microbiota transplantation - Wang, Yaru; Zhang, Zhenzhen; Liu, Bin; Zhang, Chunzhi; Zhao, Junying; Li, Xianping; Chen, Lijun (Frontiers in Microbiology, 2022)
The gestation period is critical for the health of the mother and fetus. Malnutrition or overnutrition during pregnancy may cause gestational diseases that can result in adverse pregnancy outcomes. Fecal microbiota transplantation can be used to re-establish new gut microbiota to treat a variety of diseases and construct a model to investigate the nutritional health during pregnancy. Therefore, this study investigated whether human-derived gut microbiota during pregnancy could colonize the intestines of mice. Moreover, we determined the time and method of intervention for fecal microbiota transplantation. Based on this information, a humanized mouse model of fecal microbiota transplantation was constructed to simulate the human intestinal microecology during pregnancy, and serve as a useful animal model for the study of nutritional health and disease during pregnancy. Germ-free and specific pathogen free C57BL/6J mice were selected for humanized gestational fecal microbiota transplantation and the transplantation outcomes were evaluated. The results demonstrated that the gestational intestinal microbiota colonized the intestines of mice, allowing researchers to construct a humanized mouse model of gestational fecal microbiota transplantation. The main intestinal flora of the gestational period were transplanted into germ-free mice, with the gestational flora being similar to the flora of germ-free mice after transplantation. However, antibiotics could not eliminate the original microbial flora in specific pathogen free mice, and the flora was complex and variable after fecal microbiota transplantation with little increase in abundance. Background flora had a significant impact on the outcomes assessment. The results were better in germ-free mice than in specific pathogen free mice, and after microbiota transplantation, a superior effect was observed on day 21 compared to days 7 and 14.